Profile of Cultural Intelligence of Students in Sumbawa District - Suharli, Suharli; Andriani, Nining; Sulindra, I Gusti Made; Sentaya, I Made (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
This study aims to examine the profile of cultural intelligence of junior high school students in Sumbawa district. The sample in this study amounted to 450 junior high school students in Sumbawa-NTB district. Descriptive statistics were used to determine the level of cultural intelligence of the students in this study. The level of cultural intelligence of students is reflected in the percentage of respondents’ answers to each indicator of cultural intelligence. The research instrument used a questionnaire. Test the validity and reliability of the questionnaire using IMB SPSS 26 statistics. Meanwhile, data analysis to determine the level of cultural intelligence of students was analyzed manually using the percentage formula. The results showed that from the 20 questionnaire items there were 17 items that were declared valid with a reliability level of 0.86. Furthermore, the level of cultural intelligence of students on the metacognitive indicator obtained a score of 75.63%, on the cognitive indicator a score of 57.96%, on the motivation indicator a score of 64.80%, on the behavioral indicator a score of 66.83%, and the total average score of 66.31 %. Thus, it is hoped that teachers and school principals can use the cultural intelligence of students as a reference in designing and implementing the learning process in the classroom.